Two new Oribatid mites from Costa Rica, Mixacarus turialbaiensis sp. n. and Paulianacarus costaricensis sp. n. (Acari, Oribatida, Lohmanniidae) - Fernandez, Nestor (2017)
In this paper we describe two new species belonging to the family Lohmanniidae: Mixacarus turialbaiensis sp. n. and Paulianacarus costaricensis sp. n. from Costa Rica.